The Catalan conflict: media speeches and discursive expressions of users on YouTube - Chamorro Maldonado, Miguel Alejandro (2018)
The purpose of this communication is to show the measurements made to the discursive analysis of the users who participated in the debate on the Catalan conflict in 2017, after the referendum held the same year and its incidents on YouTube. The theoretical line is based on the arguments of online participation, discursive semiotics in digital platforms, cultural convergence, YouTube's influence on society and the power of postmodernism, as well as understanding that the network is a meeting point for those who want to exhibit and watch a video, but also look for information of different types in the range of possibilities of format and style of audiovisual production. The methodological technique is a global sample in which the expressions that participate in behaviors and interactions oriented to emotional, cognitive, social and cultural inferences grouped in the analysis units whose results reflected the battle where the spirit of collective thinking is molded are inferred in which power is acquired in the digital language on the structural problems.